The Designing of Resort Hotels in Sabang - Muhammad Askal Satria (Universitas Syiah Kuala, 2019)
Every year Sabang City continues to experience an increase in the number of local and international tourists who come totravel. This increase in number was unfortunately not accompanied by an increase in temporary housing facilities found inSabang City. According to the projection table, in 2017 the number of visitors to Sabang is not comparable with the numberof available rooms which is 1672 or equivalent to 2.2:1. The lack of temporary housing facilities has the potential to hamperthe development of the tourism sector in Sabang. The refore it is necessary to build a resort hotel facility as an effort toaccommodate the increasing number of tourists visiting Sabang. The resort hotel that will be built has a tropical architecturaltheme with the concept of environmental responsiveness. This hotel was built by utilizing the natural potential containedaround the site as an attraction for tourists as potential customers. The facilities provided by this hotel are of a 3-star standardwith affordable prices for tourists from various backgrounds and economic strata. The construction of this resort hotel isexpected to be one of the supporting factors that contribute to advancing the tourism sector and can help solve the problemof lack of temporary housing for tourists in the city of Sabang.